Особливості накопичення іонів важких металів молюсками Planorbis planorbis (Gastropoda, Pulmonata) - Гураль, Р.І. (Вестник зоологии, 2013)
Проанализированы особенности накопления ионов тяжёлых металлов в организме модельного вида пресноводных моллюсков в гидротопах разного типа. За редкими исключениями, максимальные концентрации тяжёлых металлов наблюдались в раковине. Содержание тяжёлых металлов в раковине и мягком теле Planorbis planorbis (Linnaeus, 1758) в целом адекватно отражает степень загрязнения ними водной среды, что делает возможным использование этого вида в качестве биоиндикатора. The peculiarities of the organism of the fashion species of the freshwater molluscs in the water biotopes of the various types were analysed. With the rare exception the greatest consentrations of the heavy metals were observed in the shell. The content of the heavy metals in the shell and the soft body of the Planorbis planorbis (Linnaeus, 1758) in the general equivalently reflect the degree of the pollution of the water environment by the heavy metals. This lets to use the given species as the bioindicator.